Cause-specific mortality of 1-year survivors of subarachnoid hemorrhage - Miikka Korja; Karri Silventoinen; Tiina Laatikainen; Pekka Jousilahti; Veikko Salomaa; Jaakko Kaprio (2013)
To assess long-term, cause-specific mortality rates and rate ratios of the patients alive at 1 year after subarachnoid hemorrhage (SAH).The population-based, prospective, cohort study with a nested case-control design consisted of 64,349 persons (aged 25-74 years at enrollment) who participated in the National FINRISK Study between 1972 and 2007. Four hundred thirty-seven SAH cases, 233 one-year SAH survivors, and their matched intrinsic controls were identified and followed up until the end of 2009 through the nationwide Finnish Causes of Death Register. All-cause mortality rates and rate ratios of the 1-year SAH survivors and controls were the main outcome measures.Eighty-eight (37.8%) of 233 one-year SAH survivors died during the total follow-up time of 2,487 person-years (median 8.6 years, range 0.1-35.8 years). The 1-year SAH survivors had a hazard ratio of 1.96 (95% confidence interval 1.57-2.47) for death compared with the matched general population with 10 controls for each SAH survivor. One-year SAH survivors had up to 31 additional deaths per 1,000 person-years compared with controls with minimal cerebrovascular risk factors. The higher long-term risk of death among SAH survivors was attributed solely to cerebrovascular diseases, and most important modifiable risk factors for death were smoking, high systolic blood pressure (≥ 159 mm Hg), and high cholesterol levels (≥ 7.07 mmol/L).One-year SAH survivors have excess mortality, which is attributed to an exceptional risk of deadly cerebrovascular events. Aggressive post-SAH cerebrovascular risk factor intervention strategies are highly warranted.